PENERAPAN PENERAPAN STRATEGI PEMBELAJARAN THE POWER OF TWO DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 5 PADANG - Irani, Silvia; Zulfaneti, Zulfaneti; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was based on the studentsâ low understanding of mathematical concept. This resulted in the studentsâ understanding of mathematical concept embedded optimally yet one good alternative to overcome these problems in mathematics learning strategies used The Power Of Two. This study aims to determine whether students understanding of mathematical concept by using active learning strategies The Power Of Two with quiz was better than the students understanding of mathematical concept using conventional learning in class VII SMPN 5 Padang. The design used was random against subject. With population of all VII grade students SMPN 5 Padang. Sample were taken at random. VII4 classroom experiments and VII5 selected as the control class. Research instruments are quizzed and final test in the form of an essay. From the analysis of test data and the understanding of concept normally distributed homogeneously. Based on the analysis result, the average student learning outcomes experimental class 98.42 higher than the control class is 82.81. From the hypothesis done t table obtained was less than the calculed. So it can be concluded that the students understanding of mathematical concept by using active learning strategies The Power Of Two with Quiz was better than the students understanding of mathematical concept using conventional in class VII SMPN 5 Padang.Â